2013
DOI: 10.1186/1756-0500-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deposition and Ferritin Heavy Chain (Fth) Localization in Rodent Teeth

Abstract: BackgroundAn iron rich layer on the labial surface is characteristic of the enamel of rodent incisors. In order to address a role for iron content in continuously growing incisors during odontogenesis, we studied iron deposition patterns in enamel and dentine using Perls’ blue staining and ferritin heavy chain (Fth) immunolocalization. Fth expression is regulated by iron level; therefore its localization can be used as a sensitive indicator for iron deposition.ResultsSagittal sections of 4-week old rat incisor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 31 publications
6
111
0
1
Order By: Relevance
“…This is because NG 50 estimates the reference genome length based on the input contigs themselves (Ghodsi et al 2013), not on an input reference genome. This exemplifies that the overinflated NG 50 results can be inaccurate and misleading.…”
Section: Resultsmentioning
confidence: 99%
“…This is because NG 50 estimates the reference genome length based on the input contigs themselves (Ghodsi et al 2013), not on an input reference genome. This exemplifies that the overinflated NG 50 results can be inaccurate and misleading.…”
Section: Resultsmentioning
confidence: 99%
“…(12,13) Iron deficiency affects more than two billion people in the world and is one of the most common nutritional deficiencies. (14) Although iron deficiency may sometimes result from defects in the body's ability to metaboliseiron, the most common cause is inadequate iron in the diet, a deficiency that is treatable by foods and supplements which contain iron salts.…”
Section: Mechanisms Involved In Black Stainmentioning
confidence: 99%
“…[56-61] Recent retrospective studies have not shown evidence of increased thromboembolic events. Larger randomized control trials are still needed to determine the ideal dosing and timing of TXA administration in this population.…”
Section: Use Of Tranexamic Acid In Non-trauma Patientsmentioning
confidence: 99%